Irreverent Persia Invective, Satirical and Burlesque Poetry from the Origins to the Timurid Periode (10th to 15th Centuries) - Zipoli, Riccardo (Iranian Studies Series, 2015)
Poetry expressing criticism of social, political and cultural life is a vital integral part of Persian literary history. Its principal genres - invective, satire and burlesque - have been very popular with authors in every age. Despite the rich uninterrupted tradition, such texts have been little studied and rarely translated. Their irreverent tones range from subtle irony to crude direct insults, at times involving the use of outrageous and obscene terms. This anthology includes both major and minor poets from the origins of Persian poetry (10th century) up to the age of Jami (15th century), traditionally considered the last great classical Persian poet